How Sustainable Are Claims about Evidence-Based Content in Australian Courses for Preparing Special Educators? - Jennifer Stephenson; Rahul Ganguly; Coral Kemp; Catherine Salisbury (MDPI AG, 2023)
We reviewed the content of units in master's-level special and/or inclusive education courses in Australia to determine whether the content relating to instructional practices and behaviour support and intervention included evidence-based practices (practices drawn from sound research). We identified claims about evidence-based practices made in publicly available materials describing unit content and determined whether these claims were supported by the actual content described. Of the 28 courses examined, six made no claims about evidence-based practices, 19 courses included supported claims and 15 courses included unsupported claims. Interpretation of the results should be cautious given the limited material available for some courses, but overall, the results are cause for concern. We believe there is a need for formal standards for special/inclusive education courses and certification for qualified special educators in Australia.